Automated identification of relevant patient information in a physician's workstation. - Suermondt, H. J. (American Medical Informatics Association, 1993)
The introduction of computer-based patient records offers an opportunity to improve the ability of physicians to browse the medical record and to monitor patient events. We describe a methodology to identify relevant information in the patient record. This methodology combines a patient-specific physiological model with functions to determine relevance of patient information. The model consists of a qualitative representation of physiological parameters and influences, custom-tailored to a particular patient's problems, medications, and test results. We describe two applications of this model in the context of an integrated physician's workstation: automatic linking of relevant patient information for configuration of user-interface displays, and monitoring of patient events to prevent oversight of noteworthy information.